2013
DOI: 10.4028/www.scientific.net/kem.594-595.780
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Space Holder in Fabrication of Cloced-Cell Aluminium Foam

Abstract: :. In this work, the closed-cell aluminium foams were fabricated via powder metallurgy route with organic space holder which also known as carbamide (urea). Carbamide was added with aluminium powder at different compositions from 50wt% to 70wt%. Then the influences of sintering temperatures were also investigated at 500°C, 550°C and 600°C. Physical and mechanical tests were conducted on the fabricated closed cell aluminium foam samples. The result showed that the porosity inversely proportional with density, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This fact confirms that the higher the total amount of porosity in the foam, the higher the percentage of open porosity, since the cubic and irregular geometry of the used saccharose particles favors the pore aggregation and the formation of open porosity channels. Conversely, the use of spheric space-holder particles promotes the formation of a more closed porosity, as Idris et al [40] reported in their study about the manufacturing of closed-cell aluminum foams in which carbamide was used as a space holder. The interconnected porosity through the adjacent pores and the open porosity channels can be appreciated in more detail in Figure 9, which shows the pores at ×250 and the inner surfaces details of pore walls at ×500.…”
Section: Porosity Analysismentioning
confidence: 99%
“…This fact confirms that the higher the total amount of porosity in the foam, the higher the percentage of open porosity, since the cubic and irregular geometry of the used saccharose particles favors the pore aggregation and the formation of open porosity channels. Conversely, the use of spheric space-holder particles promotes the formation of a more closed porosity, as Idris et al [40] reported in their study about the manufacturing of closed-cell aluminum foams in which carbamide was used as a space holder. The interconnected porosity through the adjacent pores and the open porosity channels can be appreciated in more detail in Figure 9, which shows the pores at ×250 and the inner surfaces details of pore walls at ×500.…”
Section: Porosity Analysismentioning
confidence: 99%